Cardiac Catheterisation Interventions in Neonates and Infants Less Than Three Months - Alakhfash, Ali A. (J Saudi Heart Assoc, 2020)
INTRODUCTION: Pediatric cardiac catheterization interventions become an established way of care for selected patients with congenital heart diseases. Cardiac catheterization for neonates and small infants can be challenging. The indications for diagnostic cardiac catheterization have decreased with the advent of advanced non-invasive imaging modalities. PATIENTS AND METHOD: Between June 2012 and July 2017 patients less than three months who had cardiac catheterization in two centers were reviewed RESULTS: During the study period, 174 patients underwent interventional cardiac catheterization,83.3% of them had CHD with two-ventricle circulation and 29 patients (16.7%) had single ventricle pathophysiology. Procedures include diagnostic cath, BAS, balloon pulmonary and aortic valvuloplasty, coarctation angioplasty, and stenting procedures. The vascular access depends upon the type of procedure. All except one had general anesthesia. ICU admission was required on 106 patients (62%). Patients were divided according to the type of cardiac lesion (single versus biventricular pathology) as well as according to the type of intervention (stenting and non-stenting procedures). Comparing these groups revealed that: stent procedures and procedures for patients with single ventricle pathologies were performed at an earlier age, with more contrast, fluoro and procedure time than for non-stent procedures and procedures for patients with biventricular pathologies. Complications include transient arrhythmias in most patients, perforation of the RVOT in one and lower limb hypoperfusion in 12 patients. ICU complications include low cardiac output symptoms (LCOS) in 10 (7%), and sepsis in 8. No intra-procedure mortality. The overall survival was 94%. Ten patients died, with one early and 9 late mortality. 60% of the dead patients had PDA stenting. Reintervention varies according to the patient's diagnosis. CONCLUSION: Cardiac catheterization intervention an important modality in the management of neonates and infants with critical CHD. Well planned procedures and team expertise are essential. Stenting procedures and procedures for patients with single ventricles carries higher morbidity and mortality.